2020
DOI: 10.3390/nu12102927
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of ALDH1A Enzyme Inhibition on Helicobacter-Induced Colitis in Smad3−/− Mice are Associated with Altered α4ß7 Integrin Expression on Activated T Cells

Abstract: Many inflammatory bowel disease (IBD) patients require surgical intervention due to limited pharmacological treatment options. Antibodies targeting α4ß7, a gut-homing integrin, are one of the most promising IBD treatments. As retinoic acid (RA) regulates expression of gut-homing proteins including α4ß7 integrin, we tested if ALDH1A enzymes in the RA synthesis pathway could be targeted for IBD treatment using a potent inhibitor, WIN 18,446. Age- and sex-matched Smad3−/− mice were fed a diet with and without WIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The potential effectiveness of 5-ASA in producing significant effects through the alleviation of mucosal inflammation has been documented ( 16 18 ). Likewise, corticosteroids prove effective in mitigating inflammatory responses, exhibiting immunomodulatory effects and finding extensive applications in treatment ( 19 21 ). Glucocorticoids are commonly employed for more severe conditions than those treated with 5-ASA ( 22 ), and their administration may be escalated when 5-ASA treatment proves ineffective ( 23 ).…”
Section: Treatment Methods For Ibdmentioning
confidence: 99%
“…The potential effectiveness of 5-ASA in producing significant effects through the alleviation of mucosal inflammation has been documented ( 16 18 ). Likewise, corticosteroids prove effective in mitigating inflammatory responses, exhibiting immunomodulatory effects and finding extensive applications in treatment ( 19 21 ). Glucocorticoids are commonly employed for more severe conditions than those treated with 5-ASA ( 22 ), and their administration may be escalated when 5-ASA treatment proves ineffective ( 23 ).…”
Section: Treatment Methods For Ibdmentioning
confidence: 99%
“…The histopathology of H. bilisinduced IBD includes crypt hyperplasia, inflammatory cell infiltrates, crypt abscesses, and obliteration of normal gut architecture. In this study, the relationship between H. bilis and IBD was established by searching in PubMed, MED-LINE, and Web of Science databases, and these results were shown in Table 1 [9,[41][42][43][44][45][46][47][48][49][50][51][52][53]. Some studies clarified how H. bilis promotes IBD occurrence and development; however, few studies have summarized these mechanisms.…”
Section: H Bilis Promotes Ibd Through Inducing Aberrantmentioning
confidence: 99%
“…Various mouse models of IBD include spontaneous colitis models, chemically induced colitis models, colitis in immunodeficient mice, genetically engineered models, or any combination of these models. Recently, a newly identified murine pathogen, Helicobacter bilis ( H. bilis ), has been related to gut infection causing chronic inflammation [ 9 ]. Therefore, H. bilis has been widely used to establish IBD mouse models in many studies, but the mechanism remains unclear [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has been using a strong and specific ALDH1A inhibitor, WIN 18,446, to study the role of ALDH1A enzymes in spermatogenesis [ 21 , 22 ]. Our group has also used this inhibitor to study colitis, and showed that WIN 18,446 treatment reduced RA synthesis in vivo and suppressed colitis in an acute mouse model of IBD using Smad3 −/− mice [ 23 ]. WIN 18,446 treatment was associated with the decreased expression of the gut homing α4ß7 integrin on activated CD4 + T cells [ 23 ], which is intriguing because some of the most effective biologics for the treatment of IBD are monoclonal antibodies targeting α4ß7 integrin [ 1 ].…”
Section: Introductionmentioning
confidence: 99%